2009
DOI: 10.1002/jmri.21707
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of iron distribution between liver, spleen, pancreas, bone marrow, and myocardium by means of R2 relaxometry with MRI in patients with β‐thalassemia major

Abstract: Purpose:To investigate the correlation between the degree of hepatic, splenic, pancreatic, vertebral bone marrow (VBM), and myocardial siderosis, as expressed by relaxation rate (R2 ϭ 1/T2) values, in patients with thalassemia. Materials and Methods:R2 relaxation rate values of liver, spleen, VBM, pancreas, and myocardium were estimated in 68 consecutive transfusion-dependent patients with ␤-thalassemia major and 10 healthy controls using a respiratory triggered 16-echo Carr-Purcell-Meiboom-Gill (CPMG) spin ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 40 publications
8
84
0
Order By: Relevance
“…The iron accumulates primarily in the liver, then in the endocrine glands and only later in the heart (1,2). Increased iron deposit is cytotoxic and may cause organ dysfunction (3).…”
Section: Introductionmentioning
confidence: 99%
“…The iron accumulates primarily in the liver, then in the endocrine glands and only later in the heart (1,2). Increased iron deposit is cytotoxic and may cause organ dysfunction (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two recent studies by De Assis et al [26] and Noetzli et al [33] claim that iron deposition in pancreas follows a similar pathway with iron accumulation in cardiac muscle but occurs earlier; therefore accurate identification of iron deposition in the pancreas might serve as an early predictor of cardiac siderosis. Previous studies have found no correlation or weak correlations between pancreatic siderosis and ferritin, or between pancreatic and hepatic siderosis as expressed by any MR measurement including R 2 , R 2 * relaxometry [18][19][20][21][22][23][24] or SIR on in-phase and out-of-phase images. In accordance with these publications, we did not manage to document a statistically significant correlation between pancreatic R 2 , without fat suppression, and ferritin or hepatic R 2 .…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, no previous study has applied fat suppression in multiecho sequences for R 2 or R 2 ⁎ relaxometry for iron overloaded tissues well known to contain significant amounts of fat [18][19][20][21][22][23][24][25]. Schwenzer et al [32] have been the only group that had applied fat suppression in a multiecho gradient sequence for T2* calculation in a large cohort of 129 healthy subjects, and they found a significant correlation between hepatic T2* and ferritin (r=0.62) but no correlation between pancreatic T2* and ferritin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly the existence of factors like transfusion history, chelation therapy or co-pathology has an impact on the location and extent of cardiac iron accumulation [23,24]. Therefore, it is recommended that the decision for the start and regimen of chelation therapy should be spared for older age group patients with regular transfusion, cardiac hemosiderosis or liver fibrosis [17].…”
Section: Discussionmentioning
confidence: 99%